Incidental Thrombus in Transit Causing Embolic Stroke - Brian Malm; Paul Hermany; Alan Morrison (Case Reports in Medicine)
Thrombus in transit leading to paradoxical systemic arterial embolism is a rare echocardiographic finding in patients presenting with embolic stroke. We present a case of a patient who had an atrial thrombus in transit discovered incidentally and later suffered a fatal stroke. Etiologies of cardioembolic stroke and the use of echocardiography in diagnosis and management are briefly discussed.